Critical velocity and anaerobic paddling capacity determined by different mathematical models and number of predictive trials in canoe slalom - Messias, L. H. D.; Ferrari, H. G.; Reis, I. G. M.; Scariot, P.P. M.; Manchado-Gobatto, F. B. (Journal of Sports Science & Medicine, 2015)
The purpose of this study was to analyze if different combina-tions of trials as well as mathematical models can modify the aerobic and anaerobic estimates from critical velocity protocol applied in canoe slalom. Fourteen male elite slalom kayakers from Brazilian canoe slalom team (K1) were evaluated. Athletes were submitted to four predictive trials of 150, 300, 450 and 600 meters in a lake and the time to complete each trial was record-ed. Critical velocity (CV-aerobic parameter) and anaerobic paddling capacity (APC-anaerobic parameter) were obtained by three mathematical models (Linear1=distance-time; Linear 2=velocity-1/time and Non-Linear = time-velocity). Linear 1 was chosen for comparison of predictive trials combinations. Standard combination (SC) was considered as the four trials (150, 300, 450 and 600 m). High fits of regression were ob-tained from all mathematical models (range - R² = 0.96-1.00). Repeated measures ANOVA pointed out differences of all mathematical models for CV (p = 0.006) and APC (p = 0.016) as well as R² (p = 0.033). Estimates obtained from the first (1) and the fourth (4) predictive trials (150 m = lowest; and 600 m = highest, respectively) were similar and highly correlated (r=0.98 for CV and r = 0.96 for APC) with the SC. In summary, meth-odological aspects must be considered in critical velocity appli-cation in canoe slalom, since different combinations of trials as well as mathematical models resulted in different aerobic and anaerobic estimates.